Device for Assessing Knee Joint Dynamics During Magnetic Resonance Imaging. Issue 3 (9th August 2021) - Jogi, Sandeep P.; Thaha, Rafeek; Rajan, Sriram; Mahajan, Vidur; Venugopal, Vasantha K.; Mehndiratta, Amit; Singh, Anup
Abstract : Background: Knee assessment with and without load using magnetic resonance imaging (MRI) can provide information on knee joint dynamics and improve the diagnosis of knee joint diseases. Performing such studies on a routine MRI‐scanner require a load‐exerting device during scanning. There is a need for more studies on developing loading devices and evaluating their clinical potential. Purpose: Design and develop a portable and easy‐to‐use axial loading device to evaluate the knee joint dynamics during the MRI study. Study Type: Prospective study. Subjects: Nine healthy subjects. Field Strength/Sequence: A 0.25 T standing‐open MRI and 3.0 T MRI. PD‐T2 ‐weighted FSE, 3D‐fast‐spoiled‐gradient‐echo, FS‐PD, and CartiGram sequences. Assessment: Design and development of loading device, calibration of loads, MR safety assessment (using projectile angular displacement, torque, and temperature tests). Scoring system for ease of doing. Qualitative (by radiologist) and quantitative (using structural similarity index measure [SSIM]) image‐artifact assessment. Evaluation of repeatability, comparison with various standing stances load, and loading effect on knee MR parameters (tibiofemoral bone gap [TFBG], femoral cartilage thickness [FCT], tibial cartilage thickness [TCT], femoral cartilage T2 ‐value [FCT2], and tibia cartilage T2 ‐value [TCT2]). The relative percentage change (RPC) in parameters due to the device load was computed. Statistical Test: Pearson's correlation coefficient ( r ). Results: The developed device is conditional‐MR safe (details in the manuscript and supplementary materials), 15 × 15 × 45 cm 3 dimension, and <3 kg. The ease of using the device was 4.9/5. The device introduced no visible image artifacts, and SSIM of 0.9889 ± 0.0153 was observed. The TFBG intraobserver variability (absolute difference) was <0.1 mm. Interobserver variability of all regions of interest was <0.1 mm. The load exerted by the device was close to the load during standing on both legs in 0.25 T scanner with r > 0.9. Loading resulted in RPC of 1.5%–11.0%, 7.9%–8.5%, and −1.5% to 13.0% in the TFBG, FCT, and TCT, respectively. FCT2 and TCT2 were reduced in range of 1.5–2.7 msec and 0.5–2.3 msec due to load. Data Conclusion: The proposed device is conditionally MR safe, low cost (material cost < INR 6000), portable, and effective in loading the knee joint with up to 50% of body weight. Evidence Level: 1 Technical Efficacy: Stage 1